THE INFLUENCE OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Muhammad Abid (International Journal Multidisciplinary Science, 2024)
This research aims to determine the influence of organizational culture and job satisfaction on employee performance at Bank Negara Indonesia (BNI) Tangerang Branch Office. This research uses quantitative research. The population in this study were all employees at PT Bank Negara Indonesia (BNI), and saturated sampling was used to obtain a sample of 87 respondents. The data collection method used in this research is primary data. The primary data taken was data from answers from 87 respondents. This research shows that organizational culture has no effect on employee performance, and job satisfaction has an effect on employee performance. Simultaneously, organizational culture and job satisfaction influence employee performance. Organizational culture and job satisfaction are integrated into measuring employee work performance. If one of these things is problematic, then employees of PT Bank Negara Indonesia (Persero) Tbk, Tangerang Branch Office will not be able to maximize their performance at work, and this will, of course, affect the company in achieving its stated goals.